HUBUNGAN PERILAKU PICKY EATER DENGAN STATUS GIZI PADA BALITA DI PAUD SALMAN AL FARISI DUSUN TAWANG REJO DESA PAGUTAN KECAMATAN MANYARAN KABUPATEN WONOGIRI - Aminatul Fatayati (STIKES DUTAGAMA KLATEN, 2023)
Picky eating is one of the problems of eating disorders. The distinctive feature ofpicky eater is the lack of interest in the general food menu or avoid to try new food, sincetoddler with picky eating only interested in certain food menus. Toddler with picky eating tend to have a habit to refuse picking food so it can cause low food intake and will have an impact on nutritional status.To determine the association of picky eating behaviour to nutritional status in Early Childhood educstion Programs Salman AlFarisi hamlet Tawang Rejo village Pagutan subdistrict Manyaran regency Wonogiri.This study was an observational study with cross sectional approach. Atotal of 59 respondents were selectedusing systematic random sampling. Behaviour of picky eater were obtained from ChildEating Behaviour Questionnaire, nutritional status data were obtained from measurement of body weight which then interpreted using weight to age indicator. Data were analyzed sing Pearson Product Moment. 88.1% ofthe respondents were categorized as picky eater. 66.1% were considered to have a good nutritional status, 3.4% were classified as overnutrition and the 30.5% ofthe respondents were categorized as under-nutrition. Noassociation was found between picky eating behaviour and nutritional status of toodlersin Pagutan Manyaran Wonogiri. (p = 0,888)